Record label marketing : how music companies brand and market artists in the digital era.: how music companies brand and market artists in the digital era. (2015) - Rolston, Clyde Philip; Macy, Amy; Hutchison, Thomas W (Thomas William); Allen, Paul, 1946-
No abstract available